Oliceridine — a unique drug among opioid analgesics (Journal of Medical Science, 2020)
Oliceridine is an opioid with a different mechanism of action compared to classical opioid agonists, e.g. morphine, as it does not act through active metabolites and activates the β-arrestin pathway to a small extent, thereby reducing dangerous side effects and broadening the therapeutic window. This is particularly important as, despite the wide availability of drugs from various therapeutic groups, the effectiveness of analgesics in many patients remains low. Oliceridine is a novel and effective analgesic providing rapid analgesia, with a favourable safety and tolerability profile concerning respiratory and gastrointestinal adverse effects compared to morphine, and may provide a new treatment option for patients with moderate to severe postoperative pain where an intravenous opioid is required.